2007
DOI: 10.1093/jac/dkm064
|View full text |Cite
|
Sign up to set email alerts
|

No change in calculated creatinine clearance after tenofovir initiation among Thai patients

Abstract: We did not find renal dysfunction on tenofovir among Thai patients included in the Staccato trial. Tenofovir could be safely prescribed at a standard dosage of 300 mg once daily in the Thai population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…However, the TDF-related nephrotoxicity has hardly been evaluated in patients with small body weight, who are potentially at higher risk for larger drug exposure and thus, more severe toxicity [12][15]. Indeed, some recent studies including ours reported a higher incidence of TDF-related renal dysfunction among Asian patients with low body weight compared with previous studies on mostly Whites and African Americans with larger body weight [13], [16].…”
Section: Introductionmentioning
confidence: 66%
“…However, the TDF-related nephrotoxicity has hardly been evaluated in patients with small body weight, who are potentially at higher risk for larger drug exposure and thus, more severe toxicity [12][15]. Indeed, some recent studies including ours reported a higher incidence of TDF-related renal dysfunction among Asian patients with low body weight compared with previous studies on mostly Whites and African Americans with larger body weight [13], [16].…”
Section: Introductionmentioning
confidence: 66%
“…Indeed tenofovir molecule is controversial in numbers of studies. Someone had found that the use of long-term tenofovir resulted in a net decrease of glomerular flow filtration [26,27]; by against other showed a good renal safety of tenofovir [28][29][30]. Overall, it seems that tenofovir is not nephrotoxic in the long term at least when it is prescribed in patients without renal impairment [31].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…Some cohort studies described no significant evidence of renal dysfunction with the use of TDF [15][16][17] in contrast to the other study. 9 Most of HIV-infected patients' care in Thailand, where is a resource-limited setting, is covered by the National AIDS Program.…”
Section: Introductionmentioning
confidence: 74%
“…Median (IQR) time to renal function decline was 8 (3-13.5), 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and 11 (6-19) months, respectively, when estimated from the total number of the patients. By Kaplan-Meier analysis, median time to renal function decline was 28 (95% CI 25-30) months for eGFR criteria and 31 (95% CI 28-34) months for CCrCl criteria.…”
Section: Resultsmentioning
confidence: 99%